Circ_0062270 upregulates EPHA2 to facilitate melanoma progression via sponging miR-331-3p. Issue 3 (September 2021) - Chen, Xiaogang; Tang, Yichen; Yan, Jianna; Li, Liang; Jiang, Long; Chen, Yuchong
Highlights: Circ_0062270 silencing represses melanoma cell progression and tumor growth. Circ_0062270 interacts with miR-331-3p. EPHA2 is a target of miR-331-3p. Abstract: Background: Circular RNA (circRNA) has been confirmed to play a vital role in melanoma progression. Objective: The regulatory function of circ_0062270, a novel circRNA, in melanoma progression is unclear. Methods: Relative expression levels of circ_0062270 and microRNA (miR)-331-3p were determined using qRT-PCR. Cell counting kit 8 assay, EdU staining and flow cytometry were used to measure cell proliferation, cell cycle distribution and apoptosis. The protein levels of proliferation, apoptosis and metastasis-related markers, as well as EPH receptor A2 (EPHA2), were tested using western blot analysis. Besides, cell migration and invasion were evaluated using transwell assay. Meanwhile, the interaction between miR-331-3p and circ_0062270 or EPHA2 was confirmed by dual-luciferase reporter assay or RIP assay. Additionally, tumor xenograft models were constructed to investigate the function of circ_0062270 on melanoma tumor growth in vivo . Results: The expression of circ_0062270 was increased in melanoma tissues and cells. Knockdown of circ_0062270 inhibited proliferation, promoted apoptosis, and repressed metastasis in melanoma. Moreover, circ_0062270 could serve as miR-331-3p sponge, and miR-331-3p could target EPHA2. Furthermore, miR-331-3p inhibitor and EPHA2 overexpression reversed the inhibitory effect of circ_0062270 silencing on melanoma progression. In addition, silenced circ_0062270 also could inhibit melanoma tumor growth in vivo . Conclusion: Circ_0062270 accelerated the progression of melanoma through regulating the miR-331-3p/EPHA2 axis, suggesting that circ_0062270 might be a novel potential therapeutic target for melanoma.